Air-sea gas exchange at wind speeds up to 85 m s-1 - Krall, Kerstin Ellen; Smith, Andrew W.; Takagaki, Naohisa; Jähne, Bernd (Ocean science, 2019)
Abstract. Gas transfer velocities were measured in two high-speed wind-wave tanks (Kyoto University and the SUSTAIN facility, RSMAS, University of Miami) using fresh water, simulated seawater and seawater for wind speeds between 7 and 85 m s−1. Using a mass balance technique, transfer velocities of a total of 12 trace gases were measured, with dimensionless solubilities ranging from 0.005 to 150 and Schmidt numbers between 149 and 1360. This choice of tracers enabled the separation of gas transfer across the free interface from gas transfer at closed bubble surfaces. The major effect found was a very steep increase of the gas transfer across the free water surface at wind speeds beyond 33 m s−1. The increase is the same for fresh water, simulated seawater and seawater. Bubble-induced gas transfer played no significant role for all tracers in fresh water and for tracers with moderate solubility such as carbon dioxide and dimethyl sulfide (DMS) in seawater, while for low-solubility tracers bubble-induced gas transfer in seawater was found to be about 1.7 times larger than the transfer at the free water surface at the highest wind speed of 85 m s−1. There are indications that the low contributions of bubbles are due to the low wave age/fetch of the wind-wave tank experiments, but further studies on the wave age dependency of gas exchange are required to resolve this issue.